1994
DOI: 10.1093/rheumatology/33.11.1049
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Methotrexate and Sulphasalazine vs Methotrexate Alone: A Randomized Open Clinical Trial in Rheumatoid Arthritis Patients Resistant to Sulphasalazine Therapy

Abstract: To compare efficacy, toxicity, and the pharmacokinetics of the combination of sulphasalazine (SASP) and methotrexate (MTX) vs MTX alone in the treatment of SASP-resistant RA we conducted a controlled open clinical trial. Forty RA patients with active arthritis despite adequate SASP therapy, were allocated randomly to regimes of either SASP+MTX or MTX alone. The patients were evaluated openly by a single observer for 24 weeks. In the first 15 patients using the combination, pharmacokinetics of MTX without and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 0 publications
2
27
0
1
Order By: Relevance
“…One patient in the combination group dropped out at week 4 because of the development of an 'overlap syndrome' with leucopenia, lung abnormalities, skin lesions and anti-ds DNA antibodies. The results of this small open study suggest that the combination MTX -f-SASP is clinically superior and not more toxic than MTX alone [35]. This is currently being evaluated in large double-blind trials comparing MTX + SASP versus the individual components.…”
Section: Lin Ic a L Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…One patient in the combination group dropped out at week 4 because of the development of an 'overlap syndrome' with leucopenia, lung abnormalities, skin lesions and anti-ds DNA antibodies. The results of this small open study suggest that the combination MTX -f-SASP is clinically superior and not more toxic than MTX alone [35]. This is currently being evaluated in large double-blind trials comparing MTX + SASP versus the individual components.…”
Section: Lin Ic a L Resultsmentioning
confidence: 85%
“…In the present study circulating cytokines (IL-l/i, TNFa, IL-6, IL-1RA), soluble receptors (sIL-2R and sTNFR) and the production of IL-l/i, TNFa and IL-1RA by PBMNC were longitudinally assessed in patients with active RA enrolled in a randomized open trial of MTX combined with SASP vs MTX alone [35]. Potential different effects of combination (MTX-f SASP) and single drug (MTX) therapy on the cytokine network could be relevant since: (a) MTX + SASP seemed superior and not more toxic than MTX alone in the clinical study [35] and (b) previous reports had suggested that MTX and SASP may differ in their modulation of circulating cytokines and cytokine production [24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, given the large difference to study the steady state of SASP, trough levels reflect well enough the levels of SASP and its major metabolites to which the body is exposed. The improved clinical response to the combination of MTX and SASP, previously reported in a clinical trial [22 ], cannot therefore be explained by altered pharmacokinetics of MTX or SASP and its major metabolites.…”
Section: Introductionmentioning
confidence: 84%